2021
DOI: 10.3390/ijms22136715
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hydrogen Sulfide Plays an Important Role by Regulating Autophagy in Diabetic-Related Diseases

Abstract: Autophagy is a vital cell mechanism which plays an important role in many physiological processes including clearing long-lived, accumulated and misfolded proteins, removing damaged organelles and regulating growth and aging. Autophagy also participates in a variety of biological functions, such as development, cell differentiation, resistance to pathogens and nutritional hunger. Recently, autophagy has been reported to be involved in diabetes, but the mechanism is not fully understood. Hydrogen sulfide (H2S) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 99 publications
(117 reference statements)
0
13
0
Order By: Relevance
“…Lv et al discussed the role of exogenous hydrogen sulfide (H 2 S) in regulating autophagy in diabetic-related diseases [8]. H 2 S is a signal transducer in many biological functions, including antiapoptosis, antioxidative stress, blood vessel relaxation, blood pressure reduction, and the anti-inflammatory process.…”
mentioning
confidence: 99%
“…Lv et al discussed the role of exogenous hydrogen sulfide (H 2 S) in regulating autophagy in diabetic-related diseases [8]. H 2 S is a signal transducer in many biological functions, including antiapoptosis, antioxidative stress, blood vessel relaxation, blood pressure reduction, and the anti-inflammatory process.…”
mentioning
confidence: 99%
“…In addition, L-cystine can be converted into 3-mercaptopyruvate (3-MP) catalyzed by cysteine aminotransferase (CAT) by transferring amine to α-ketoglutarate to form 3-mercaptopyruvate (3-MP). Finally, 3-MP can be converted into H 2 S catalyzed by 3-MST (Figure 2) [32][33][34]. Studies have shown that H 2 S is involved in various physiological processes, including inflammatory response, energy metabolism, oxidative stress, mitochondrial biogenesis, and neuroregulation [35][36][37][38].…”
Section: Overview Of Hydrogen Sulfidementioning
confidence: 99%
“…Hydrogen sulfide (H 2 S), the third member of the endogenous gasotransmitter family along with nitric oxide (NO) and carbon monoxide (CO), is generated from L-cysteine (Cys) by cystathionine-β-synthase (CBS) and cystathionine-γ-lyase (CSE) and converted within different organs and tissues. As a signal molecule, H 2 S plays a critical role in numerous physiological and pathological processes, such as regulation of inflammation, vasodilation, apoptosis, and neuromodulation. However, abnormal levels of H 2 S in living systems can cause a variety of diseases, including diabetes, Down’s syndrome, Alzheimer’s disease, and cirrhosis of the liver. Therefore, it is indispensable to develop highly sensitive and selective detection methods for monitoring the level of endogenous H 2 S in complicated biological systems.…”
Section: Introductionmentioning
confidence: 99%